Image-based assessment of aortoiliac aneurysm anatomical characteristics in patients from the global iliac branch study - Bresler, Alina-Marilena; Panthofer, Annalise; Kuramochi, Yuki; Olson, Sydney L.; Eagleton, Matthew; Schneider, Darren B.; Lyden, Sean P.; Blackwelder, William C.; Uhl, Christian; Bischoff, Moritz; Matsumura, Jon S.; Böckler, Dittmar (Langenbeck's archives of surgery, 2024)
Endovascular repair is the preferred treatment for aortoiliac aneurysm, with preservation of at least one internal iliac artery recommended. This study aimed to assess pre-endovascular repair anatomical characteristics of aortoiliac aneurysm in patients from the Global Iliac Branch Study (GIBS, NCT05607277) to enhance selection criteria for iliac branch devices (IBD) and improve long-term outcomes.
Online veröffentlicht: 23. April 2024
Gesehen am 10.10.2024